Viruses and bacteria in acute asthma exacerbations - A GA2LEN-DARE* systematic review - (:unkn) unknown (WILEY, 2011)
P>A major part of the burden of asthma is caused by acute exacerbations. Exacerbations have been strongly and consistently associated with respiratory infections. Respiratory viruses and bacteria are therefore possible treatment targets. To have a reasonable estimate of the burden of disease induced by such infectious agents on asthmatic patients, it is necessary to understand their nature and be able to identify them in clinical samples by employing accurate and sensitive methodologies. This systematic review summarizes current knowledge and developments in infection epidemiology of acute asthma in children and adults, describing the known impact for each individual agent and highlighting knowledge gaps. Among infectious agents, human rhinoviruses are the most prevalent in regard to asthma exacerbations. The newly identified type-C rhinoviruses may prove to be particularly relevant. Respiratory syncytial virus and metapneumovirus are important in infants, while influenza viruses seem to induce severe exacerbations mostly in adults. Other agents are relatively less or not clearly associated. Mycoplasma and Chlamydophila pneumoniae seem to be involved more with asthma persistence rather than with disease exacerbations. Recent data suggest that common bacteria may also be involved, but this should be confirmed. Although current information is considerable, improvements in detection methodologies, as well as the wide variation in respect to location, time and populations, underline the need for additional studies that should also take into account interacting factors.
Keywords: asthma exacerbation; atypical bacteria; detection method; PCR; respiratory virus; RESPIRATORY SYNCYTIAL VIRUS; HUMAN METAPNEUMOVIRUS INFECTION; MYCOPLASMA-PNEUMONIAE INFECTIONS; COMMUNITY-ACQUIRED PNEUMONIA; POLYMERASE-CHAIN-REACTION; HUMAN CORONAVIRUS NL63; CHLAMYDIA-PNEUMONIAE; VIRAL-INFECTIONS; TRACT INFECTIONS; YOUNG-CHILDREN